Homicides and Maltreatment‐related Deaths of Disabled Children: A Systematic Review. (5th September 2019) - Frederick, John; Devaney, John; Alisic, Eva
Abstract : This article aims to systematically review the empirical literature in relation to the homicides and maltreatment‐related deaths of disabled children in order to better understand the risk factors and to assess support for the explanatory theories posited. These theories include: (1) the stress of caregiving; (2) altruistic intent; (3) lack of bonding with the child; (4) the challenging behaviours the child; (5) cultural beliefs about disabled children; and (6) evolutionary imperatives. Systematic searching techniques were used to retrieve relevant research articles in six electronic databases: AMED, CINAHL, Criminal Justice Abstracts, Medline (PubMed), PsycINFO and SCOPUS. The issue of a child being disabled was identified as a risk factor in most reviewed articles, however the definition of the term 'disability' was not consistent nor was there a consistent approach to recording children's disability. A range of potential risk factors were found, relating to the child, the perpetrator and the environment, with the pathway to harming the child involving an interactive process between each of these. The stress of caregiving and altruistic theories were the two most common explanations for homicides and maltreatment‐related deaths of disabled children, although a combination of theories may provide a more comprehensive explanation of these complex events. 'This article aims to systematically review the empirical literature in relation to the homicides and maltreatment‐related deaths of disabled children' Key Practitioner Messages: Coordination of clear care pathways for families with disabled children, including the provision of support and counselling. Improved professional awareness of the needs of disabled children and understanding that these needs may not coincide with those of their parents or carers. Provision of opportunities for respite to enable parents of disabled children to continue their task of caring. Need for consistent data on disabled children to be collected through existing child death review processes and the criminal justice system.